Process design testing using simulation : a thesis presented in partial fulfilment of the requirements for the degree of Master in Technology in Engineering and Automation at Massey University - Martin, Nicholas Kenneth Lamie (Massey University, 2004)
PROGRAMME OVERVIEW The research described here, 'Design Testing Using Simulation,' is part of the larger programme 'Remote Process Performance Monitoring and Process Design Auditing'. The goal of this is to provide SchemNZ Ltd with the expertise and technological capability to remotely (internationally) monitor and diagnose the performance of processing and manufacturing plants. This will permit the client companies to schedule maintenance of equipment rather than react to unexpected equipment failures. In addition, it will allow the client companies to retain trained staff locally rather than attempt to duplicate skills in each international market. Project Description Specifically this project investigates the use of process simulation software to audit process designs before construction and in particular, before overseas shipping. By trialing the software on a case study the company will gain confidence in the ability of the software to highlight problems with process designs. Although the theoretical background for modelling and simulation has existed for some time, the application of these techniques is only becoming widely feasible with the advent of computers. Furthermore, the techniques are not yet as rigorous as those used in more traditional methods. A large part of this project therefore is concerned with building techniques and systems that will enable further modelling to proceed in a high-quality fashion. The results of the simulation while important, are not the driving factor in this project. Rather the creation of a logical framework that can be applied to additional projects and the validation of the model's usefulness are the primary goals for this research. This approach will lead to an integration of modelling techniques providing a system that allows useful simulations to be created quickly and easily.
Pagination misnumbered.
Keywords: Computer simulation; Engineering design; Reliability (Engineering); Fault location (Engineering); Wrapping machines -- Reliability; Electric motors, Induction